Latino Students' Transition to Middle School: Role of Bilingual Education and School Ethnic Context. (22nd April 2014) - Hughes, Jan N.; Im, MyungHee; Kwok, Oi‐man; Cham, Heining; West, Steven G.
<x xml:space="preserve">Abstract</x> Participants were 204 academically at‐risk Latino students recruited into a study when in first grade and followed for 9 years. Using piecewise latent growth curve analyses, we investigated trajectories of teacher‐rated behavioral engagement and student‐reported school belonging during elementary school and middle school and the association between trajectories and enrollment in bilingual education classes in elementary school and a change in school ethnic congruence across the transition to middle school. Overall, students experienced a drop in school belonging and behavioral engagement across the transition. A moderating effect of ethnic congruence on bilingual enrollment was found. A decline in ethnic congruence was associated with more positive trajectories for students previously enrolled in bilingual classes but more negative trajectories for nonbilingual students.